MENINGKATKAN HASIL BELAJAR LISTRIK DINAMIS MELALUI MODEL TGT DENGAN PERMAINAN CERDAS CERMAT - Sidiq Heri Susanto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2018)
Abstract: The aim of the research is to describe the implemenation of the use TGT model by applying Cerdas Cermat (Smart and Precise) Quiz to Increase the IXE SMP Negeri Sukorambi students’ learning achievement on dynamic electricity in the 2017/2018 Academic Year. Classroom Action Research was Designed by applying TGT Learning Model in Cerdas Cermat Quiz. The research steps was conducted by making small group the students at the beginning. Then, group discussion, presentation of group discussion result, and answering problems exercise. The result of Grade IXE SMPN Sukorambi science daily examination was still low, it was around 30%. It was probably because of the weakness of learning activity which was caused by uninteresting teaching model. Keywords: TGT, Cerdas cermat, Learning achievement